Pneumatic Positioning Control System Using Constrained Model Predictive Controller: Experimental Repeatability Test - Sulaiman, Siti Fatimah; Faudzi, Ahmad Athif; Khairuddin, Osman; Samsudin, Sharatul Izah; Sulaiman, Noor Asyikin; Zainal Abidin, Amar Faiz; Rahmat, M. F. (Institute Of Advanced Engineering And Science (IAES), 2021)
Most of the controllers that were proposed to control the pneumatic positioning system did not consider the limitations or constraints of the system in their algorithms. Non-compliance with the prescribed system constraints may damage the pneumatic components and adversely affect its positioning accuracy, especially when the system is controlled in real-time environment. Model predictive controller (MPC) is one of the predictive controllers that is able to consider the constraint of the system in its algorithm. Therefore, constrained MPC (CMPC) was proposed in this study to improve the accuracy of pneumatic positioning system while considering the constraints of the system. The mathematical model of pneumatic system was determined by system identification technique and the control signal to the valves were considered as the constraints of the pneumatic system when developing the controller. In order to verify the accuracy and reliability of CMPC, repetitive experiments on the CMPC strategy was implemented. The existing predictive controller, that was used to control the pneumatic system such as predictive functional control (PFC), was also compared. The experimental results revealed that CMPC effectively improved the position accuracy of the pneumatic system compared to PFC strategy. However, CMPC not capable to provide a fast response as PFC